The Portuguese slave trade in early modern Japan - De Sousa, Lucio, 1978- (Leiden ; Boston)
xiv, 594 sayfa
Keywords: “In The Portuguese Slave Trade in Early Modern Japan : Merchants, Jesuits and Japanese, Chinese, and Korean Slaves Lucio de Sousa offers a study on the system of traffic of Japanese, Chinese, and Korean slaves from Japan, using the Portuguese mercantile networks; reconstructs the Japanese communities in the Habsburg Empire; and analyses the impact of the Japanese slave trade on the Iberian legislation produced in the 16th and first half of the 17th centuries“ --